A multilevel boost DC-DC converter with MPPT algorithm for the rooftop PV system of the urban railway Nhon - Hanoi Station - Tran Hung Cuong; An Thi Hoai Thu Anh (Journal of Applied Science and Engineering)
Photovoltaic generators constantly change their maximum power point (MPP) because solar radiation and temperature at different times of the day are always different. The boost DC-DC converter used in energy conversion is controlled when solar radiation and environmental temperature changes are complex. These difficulties make it challenging to design control laws. Fast and reliable step-up DC-DC converters face many obstacles when applied in the field of high-capacity urban trains, causing the current quality of the conversion process to be limited. This paper proposes a multilevel boost DC-DC converter based on MMC configuration, applying the PWM modulation method and INC maximum power point tracking (MPPT) algorithm. MMC boost DC-DC converter can provide an N times conversion ratio and has a much lower operating frequency than conventional Boost Converter. The process of evaluating the effectiveness of the proposed converter configuration and the algorithm is performed on Matlab/Simulink software, and the output parameters of the conversion process are compared with a conventional Boost DC-DC converter based on published analyses.